Awareness of Employee Compensation and its Effect on Employee Motivation - Muneeb, Ataullah; Ahmad, Ali (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
Motivation of the employees plays an essential role to help an organization achieve effectively the objectives in terms of productivity and commitment of its employees. Considering the importance of employees’ motivation, we conducted a research in Nangarhar province of Afghanistan to find whether employees are really affected by the compensation. In other words, what factors can influence the motivation of employees within a company? The data for the study is randomly obtained from 350 employees of distinct private and public organizations through five-likert scale adopted questionnaire. To obtain consistent study results, the ordinary least square an econometric assessment method was used. The results show that rewards have positive and statistically significant impacts on the motivation of employees. Our findings also show that the impact on employee motivation is positive on financial and non-financial benefits. This means that organizations provide their employees with both financial and non-financial benefits, thus strengthening employee motivation. However, the findings also indicate that intrinsic rewards, extrinsic rewards, and job satisfaction have a considerable influence on employee motivation. Therefore, we strongly recommend both private and public organizations to motivate their employees through compensations.